Evaluating video modeling and video modeling with video feedback to enhance the performance of competitive dancers. (10th November 2019) - Quinn, Mallory; Narozanick, Taylor; Miltenberger, Raymond; Greenberg, Lori; Schenk, Merritt
Abstract : This study evaluated the use of video modeling and video modeling plus video feedback to enhance four adolescents' performance of a dance movement. Intervention was evaluated in a multiple baseline across participants design. This study found that video modeling enhanced performance from baseline, but the addition of video feedback produced further increases. For one participant, improvement was dependent on the perspective of the video model. Implications of these findings and suggestions for future research are discussed.